Building a Private Islamic Higher Education Format in Facing Transformation Into a Private Islamic Religious Institute in Jambi Province - Maisah Maisah; Norainun Norainun (Dinasti Publisher, 2022)
Building the format for the transformation of Islamic Higher Education into a Private Islamic Institute is the target of three Private Islamic Higher Education under the Provincial Kopertais XIII Environment. Therefore, each PTAIS strives with all its might to meet the various requirements that have been determined, even though here and there there are still various obstacles faced such as it is still difficult to find Human Resources or teaching staff who are liner S1 and S2 in accordance with the Program Existing and future studies. In addition, there are still inadequate facilities and infrastructure from some PTAIS and other related matters. However, efforts will still be made to fulfill it so that what is desired can be achieved and realized.